Effect of Bacillus thuringiensis on the biological characteristics of the predator Orius insidiosus Say (Hemiptera: Anthocoridae) feeding on eggs of Plutella xylostella L. (Lepidoptera: Plutellidae) - Goulart, Roberto Marchi; De Bortoli, Sergio Antonio; Vacari, Alessandra Marieli; Laurentis, Valéria Lucas; Veiga, Ana Carolina Pires; De Bortoli, Caroline Placidi; Polanczyk, Ricardo Antonio (BioAssay, 2015)
The diamondback moth (Plutella xylostella) is considered one of the most important pests of cruciferous crops (Brassicaceae) around the world. The moth occurs all year round in Brazil, where it is mainly managed by chemical control because of its convenience and quick onset of action. The indiscriminate use of pesticides affects non-target organisms and has also been associated with increased resistance ratio of P. xylostella populations. These concerns have thus sparked interest in the use of alternative control strategies, which include the use of entomopathogenic microorganisms such as Bacillus thuringiensis and predators such as Orius insidiosus. The aim was to evaluate the effect of B. thuringiensis (B. thuringiensis aizawai GC 91, Agree®) on the biological characteristics of O. insidiosus. The predators were fed eggs of P. xylostella treated with distilled water (control) or with a suspension of B. thuringiensis at a concentration of 0.7 g/0.5 L. The following biological aspects were evaluated: the duration, survival rate, and consumption of the nymphal period; and the consumption, number of eggs per female, and egg viability for adult insects. Fertility life table parameters were also evaluated for eggs with and without B. thuringiensis treatment. The results showed that O. insidiosus parameters, such as duration of the second nymphal instar, nymph consumption, and female longevity were affected by the presence of B. thuringiensis in the treated eggs. Females fed with treated eggs showed a lower progeny number, which consequently led to a lower population growth rate.